2019
DOI: 10.1158/1055-9965.epi-18-0893
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cytokine Profile to Predict Response to Intravesical BCG with or without HS-410 Therapy in Patients with Non–muscle-invasive Bladder Cancer

Abstract: Background: Despite extensive research to identify biomarkers of response in patients with non-muscle-invasive bladder cancer (NMIBC), there is no biomarker to date that can serve this purpose. Herein, we report how we leveraged serial urine samples to query a panel of cytokines at varying time points in an attempt to identify predictive biomarkers of response in NMIBC. Methods: Serial urine samples were collected from 50 patients with intermediate-or high-risk NMIBC enrolled in a phase II study, evaluating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Beginning with the favorable response of bacillus Calmette-Guérin (BCG) intravesical instillation for BCa reported in 1976, the door of immunotherapy for BCa was gradually opened [8]. To date, BCG, together with pirarubicin and other chemotherapeutics, has been regarded as the standard adjuvant treatment for nonmuscle invasive bladder cancer (NMIBC), which accounts for approximately 70% of BCa [9,10]. Although the therapeutic effect of BCG in NMIBC is significant and the tumor-specific immunity induced by BCG has been extensively studied, the mechanisms remain unclear owing to the multiple biological processes involved, including congenital immunity and acquired immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning with the favorable response of bacillus Calmette-Guérin (BCG) intravesical instillation for BCa reported in 1976, the door of immunotherapy for BCa was gradually opened [8]. To date, BCG, together with pirarubicin and other chemotherapeutics, has been regarded as the standard adjuvant treatment for nonmuscle invasive bladder cancer (NMIBC), which accounts for approximately 70% of BCa [9,10]. Although the therapeutic effect of BCG in NMIBC is significant and the tumor-specific immunity induced by BCG has been extensively studied, the mechanisms remain unclear owing to the multiple biological processes involved, including congenital immunity and acquired immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to predict response to BCG treatment also include the use of urinary and tissue molecular markers [24][25][26][27]. Unfortunately, none of them has yet entered routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported the urinary cytokine profiles soon after BCG instillation. The most consistent of these surrogate chemokines of IFN activation are CXCL10, IFN␥, IL-1, IL-6, IL-10, IL-2, TNF␣ and IL-12 [18,19]. Urinary levels of these chemokines constitute the primary indicators of the magnitude of IFN activation and/or immune cell recruitment.…”
Section: Discussionmentioning
confidence: 99%